Perlindungan Hukum Terhadap Pemegang Sertifikat Tanah Elektronik - Haris, Bilqist; I, Arfa; Hepni, Aswari (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
This study aims to analyze the forms of legal protection and legal certainty afforded to holders of electronic land certificates. It employs a normative juridical method with statutory, conceptual, and historical approaches. The findings indicate that legal protection for holders of electronic land certificates is firmly grounded within the Indonesian legal system, provided that no disputes or legal claims arise concerning the land in question. Electronic land certificates are recognized as valid proof of ownership under the Law on Electronic Information and Transactions, particularly Article 6, which affirms the equivalence of electronic documents with written documents. Further reinforcement is provided by Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency Number 3 of 2023, which governs the validity of electronic land certificates. From a security perspective, the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency has undertaken preventive measures against cybercrime risks through cooperation with the National Cyber and Crypto Agency, including the implementation of electronic signatures, hash code technology, and QR codes to ensure authenticity, integrity, and ease of access. In terms of legal certainty, electronic land certificates possess evidentiary strength equivalent to conventional written documents, including their printed versions, and are admissible in judicial proceedings, provided that the electronic data remain intact, unaltered, and consistent with the records contained in the land registry.